Innovation in business models and chain wide learning for market inclusion of smallholder producers - Proctor, E.J.; Vorley, B. (2008)
The potential for modern agribusiness to promote broad-based economic growth in developing and emerging market economies is significant. Food retailers, wholesalers, and processors have the potential to link smallholder producers to dynamic domestic and regional markets. They can contribute technical and managerial capacity building and investment. However, this potential is often underutilized, and in many countries, smallholder producers and small- and medium-scale enterprises are relegated to lower-value markets. While agribusiness is not, nor should it be, driven primarily by a development imperative, the retail and processing stages rarely see the reach of their actions at the production level, including the implications for smallholder producers. Furthermore, many recent initiatives, often working with development partners, seldom result in any lasting economic empowerment or sustained market engagement of smallholder farmers or their organizations. In many countries, there is little policy dialogue between the private and public sectors and other ket stakeholders, including farmers' organizations and civil society. This paper explores the business challenge of and case for smallholder producers' market inclusion. It looks at some of the evidences that demonstrates how business models and business processes can succeed in securing market inclusion. It includes producer-and buyer-driven business models, the development of new market intermediaries, changes in mainstream procurement policy, the development of domestic codes of good business practice, and global initiatives. This paper draws largely on business models and policy innovation from empirical research, case studies, and country-level multistakeholder chainwide learning events undertaken through a global program entitled Regoverning Markets program.
Keywords: Smallholder producers; Business models; Agribusiness development model; Regoverning markets; Market inclusion